The economic case for global vaccinations: An epidemiological model with international production networks - Cem Çakmaklı; Selva Demiralp; Sebnem Kalemli-Ozcan; Sevcan Yeşiltaş; Muhammed Ali Yıldırım (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
COVID-19 pandemic had a devastating effect on both lives and livelihoods in 2020. The arrival of effective vaccines can be a major game changer. However, vaccines are in short supply as of early 2021 and most of them are reserved for the advanced economies. We show that the global GDP loss of not inoculating all the countries, relative to a counterfactual of global vaccinations, can be higher than the cost of manufacturing and distributing vaccines globally. We use an economic-epidemiological framework that combines a SIR model with international production and trade networks. Based on this framework, we estimate the costs for 65 countries and 35 sectors. Our estimates suggest that up to 49 percent of the global economic costs of the pandemic in 2021 are borne by the advanced economies even if they achieve universal vaccination in their own countries.
Keywords: E61; F00; C51; 330; COVID-19; Sectoral Infection Dynamics; Globalization; International I-O Linkages